2019
DOI: 10.2147/cia.s195878
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exercise Training Induced Changes In Nuclear Magnetic Resonance-Measured Lipid Particles In Mild Cognitively Impaired Elderly African American Volunteers: A Pilot Study</p>

Abstract: PurposePoor cardiorespiratory fitness (CRF) is linked to cognitive deterioration, but its effects on lipid heterogeneity and functional properties in older African American (AA) subjects with mild cognitive impairment (MCI) need elucidation. This study determined whether exercise training-induced changes in blood lipid particle sizes (LPS) were associated with CRF determined by VO2Max in elderly AAs with MCI. Given the pivotal role of brain-derived neurotrophic factor (BDNF) on glucose metabolism, and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Five studies focused on the effect of aerobic training (four studies of running [ 12 , 17 , 26 , 27 ] and one study on walking [ 11 ]) on BDNF; two studies focused on the effect of running on hippocampus volume [ 28 , 29 ], and five studies included the effect of aerobic training (aerobic dance [ 13 , 30 ], Baduanjin exercise [ 31 ], and running [ 32 , 33 ]) on brain activity (e.g., event-related potential). The characteristics of the 12 studies regarding clinical characteristics, aerobic training protocol, and results are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies focused on the effect of aerobic training (four studies of running [ 12 , 17 , 26 , 27 ] and one study on walking [ 11 ]) on BDNF; two studies focused on the effect of running on hippocampus volume [ 28 , 29 ], and five studies included the effect of aerobic training (aerobic dance [ 13 , 30 ], Baduanjin exercise [ 31 ], and running [ 32 , 33 ]) on brain activity (e.g., event-related potential). The characteristics of the 12 studies regarding clinical characteristics, aerobic training protocol, and results are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…MCI diagnosis in two studies [ 17 , 31 ] was based on the Peterson diagnostic criteria for MCI [ 3 ], whereas 10 studies [ 4 , 11 , 12 , 13 , 26 , 28 , 30 , 32 , 33 ] used the neuropsychological test battery and clinical criteria for MCI [ 34 ]. Mini-Mental State Exam (MMSE) scores of MCI subjects were reported in only eight studies (between 21 and 30, see Table 1 ) [ 11 , 12 , 28 , 29 , 30 , 32 , 33 ], and Montreal Cognitive Assessment (MoCA) scores were reported in only five studies (between 19 and 25, see Table 1 ) [ 13 , 29 , 30 , 31 , 32 ]. The control groups were usual care only in six studies [ 4 , 11 , 13 , 29 , 30 , 32 ], stretch training in five studies [ 12 , 17 , 26 , 28 , 33 ], and usual physical activity in one study [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations